+0  
 
0
74
2
avatar+245 

\(x^2 -2x + 3 - 2i\sqrt{3} =0\)

 

Hello! How would I go about solving this particular equation? Factoring this seemed awful, I tried factoring out sqrt(3) out of 3 and 2i*sqrt(3) but ended up with nothing useful since the i is still there. Using the quadratic formula gave me a complex number in the root sign and I'm not sure how to handle that. What about if the x^2 had a i attached to it? So this one for instance:

 

\(ix^2 -2x + 3 - 2i\sqrt{3} =0\)

 

Thanks!

Quazars  Oct 12, 2017
Sort: 

2+0 Answers

 #1
avatar+79819 
+1

x^2  + 2x  +  3  -2i√3  = 0          rearrange as

 

x^2  +  2x   =   -3 + 2i√3           

 

Take   1/2 the coefficient on x = 1......square it  = 1   and add to both sides

 

x^2 + 2x + 1  =  -3  + 2i√3  + 1       factor the left side....simplify the right side

 

( x + 1)^2  = -2 + 2i√3   factor the right side

 

(x + 1)^2   =  2 (i√3 - 1)     take both roots

 

x + 1  =  ±√ [ 2  (i√3 - 1) ]     subtract 1 from both sides

 

x  =    ±√ [ 2  (i√3 - 1) ]  -   1

 

 

cool cool cool

CPhill  Oct 12, 2017
 #2
avatar+245 
0

Oh... is there no way to simplify that? It seems like a very messy answer. How about the second case with an i coefficient infront of the x^2 term? thanks

Quazars  Oct 13, 2017

15 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details